Digital Business Business Algorithms, Cloud Computing and Data Engineering - Patnaik, Srikanta; Yang, Xin-She; Tavana, Madjid; Popentiu-Vlădicescu, Florin; Qiao, Feng (Lecture Notes on Data Engineering and Communications Technologies, 2019)
This edited book presents contributions from three different areas: cloud computing, digital mess and business algorithms on a single platform, i.e. Digital Business. The book is divided into four sections: (i) Digital Business Transformation, (ii) Cloud Computing, (iii) IOT & Mobility, and (iv) Information Management & Social Media, which are part of a holistic approach to information management and connecting the value chains of businesses to derive more throughput in the entire business ecosystem. Digital business is a niche area of computer science and business management, and its dimension is vast - it includes technologies such as cloud computing, Internet of Things, mobile platforms, big data applied in areas like ERP, data mining and business intelligence. Digital technologies have also challenged existing business models and will continue to do so. One of the key driving forces is the capacity of innovation and the commercialization of information and communication technologies. Providing insights into the new paradigm of digital business, the book is a valuable resource for research scholars, academics and professionals.